Cognate Object dalam Bahasa Jepang: Bentuk dan Contoh - Aritonang, Betty Debora; Meilantari, Ni Luh Gede (Jurnal Bahasa Asing, 2024)
Syntax is concerned with how sentences are constructed. Language users employ a unique variation that allows for the formation of elements in sentences. Subject, verb, object, complement, and adverb are some sentence structure components that catch the attention of syntax. This research will concentrate on objects, particularly cognate objects, among the many sentence structures studied from syntax. Although the Japanese language has a cognate object similar to English, there is a slight difference. This is because the object comes before the predicate in the Japanese sentence pattern. As a result, this paper will look at how cognate object forms in Japanese. Some of the facts in the discussion suggest that the cognate object in Japanese is significantly different from the cognate object in English. This is due to the non-referential and non-accusative nature of the cognate object in Japanese. In Japanese, cognate object forms based on verbs have nearly the same qualities as verbs.